Ejercicio profesional - Acevedo, Eduardo; Varzi, Pablo; Vidal y Fuentes, Alfredo; Prado, P.; Jiménez de Aréchaga, Justino E. (Boletín Consejo Nacional de Higiene, 1911)
Reglamentación del ejercicio de la profesión de Médico Veterinario.